DEIKSIS DALAM INJIL MARKUS (ANALISIS PRAGMATIK) - KAIRUPAN, REGINA GIOVANIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTS This research is entitled â€œDeiksis Dalam Injil Markus (Analisis Pragmatik)â€. There are 5 types of deixis, those are: person deixis (first person, second person, and third person), place deixis, time deixis, discourse deixis, and social deixis. Deixis belongs to pragmatics. The word deixis come from the Greek deiktikos, which means, â€žpointingâ€Ÿ. The objectives of this research are to identify and classify the types of deixis and to analyze the use of deixis in the Gospel of Mark. The method used in this research was is descriptive method. The data were identified, classified and analyzed descriptively. The data were analyzed based on Levinson theory. The result of this research shows there are five types of deixis that could be found in the Gospel of Mark. They are person deixis (first person: I, me, and our second person: you, your, youâ€Ÿr brotherâ€Ÿs, and third person: he, his), place deixis: (home, marketplace, here, mountain, hometown, gethsemane, courtyard), time deixis: (when), discourse deixis: (that and this, and social deixis: tax collectors, disciples, The Lord, teacher). It is expected that this research will help the students and the other readers to learn the pragmatics aspect, especially about deixis. Â Keyword : Deixis, Gospel of Mark, Pragmatics, Injil Markus.